Representasi Simbol Budaya Ulos Batak dalam Branding Instagram @tobatenun sebagai Citra Budaya Pop Kontemporer - Widyah Malika; Nuraida .; Lilis Sukmawati (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This research is entitled "Representation of Batak Ulos Cultural Symbols in Instagram Branding @tobatenun as a Contemporary Pop Culture Image". This research discusses how the ulos cultural symbol is represented in digital media which has experienced a shift in the meaning of ulos which not only functions as a symbol of customs and rituals, but is also present in the modern realm through the creative industry and social media. Digital branding becomes a new space for local culture to be re-presented in a form that is more relevant to the times. This research uses a qualitative method with a Roland Barthes semiotic analysis approach, with data in the form of ten Instagram posts @tobatenun for the period June 2025 - March 2026 which were analyzed through three stages, namely denotation, connotation, and myth. Based on the analysis that has been done, it shows that ulos is represented as a cultural symbol that has experienced an expansion of meaning. Denotatively, ulos is displayed as a woven cloth with a typical Batak motif. Connotatively, ulos represents identity, elegance, and cultural aesthetic values. At the myth level, ulos is interpreted as a modern, flexible cultural symbol and has become part of a contemporary lifestyle without losing its traditional values. Overall, this research shows that the Instagram branding of @tobatenun has successfully shaped the image of ulos as contemporary pop culture through modern and communicative visuals. Ulos is not only preserved as a cultural heritage but also revived as a relevant identity in the digital age.